Social inequalities and Health: new reflections in front of Bauman and Dalrymple (Research, Society and Development, 2020)
Social inequality is a relevant phenomenon for the Human and Social Sciences, and Health Sciences, especially for Public Health, given the intercession of these areas when dealing with community realities. Therefore, this essay seeks to carry out a theoretical-critical analysis about social inequalities, their repercussions on Public Health and how new social theories help to interpret this phenomenon. For that, a previous explanation was made about the concept of Social Inequality, followed by a synthesis about Social Inequality in Health; finally, it proceeded with a critical analysis of the theoretical framework studied, connecting the “liquid modernity” of the Polish sociologist Zygmunt Bauman with the concept of underclass by the British psychiatrist and essayist Theodore Dalrymple, contemplating the multifacets of social inequalities in health in the face of conjunctures current Public Health. From the discussion of the theme, it was clear how the current culture of liquidity, together with the action of underclasses in their individualism, can foster the maintenance of social inequalities and their many facets, including in Public Health. Therefore, it is urgent to rethink actions to combat social inequalities, incorporating new perspectives, such as liquid modernity and analyzing the way the State institutionalizes the misery of underclasses.